Collective Bargaining : A Response to the Recession in Industrialised Market Economy Countries - Beaulieu, Paul (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Collective Bargaining : A Response to the Recession in Industrialised Market Economy Countries," by B.I.T.